1973
DOI: 10.1073/pnas.70.11.3094
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Cell Mutant with a Temperature-Sensitive Leucyl-Transfer RNA Synthetase

Abstract: A cell mutant of the Chinese hamster ovary line, which is temperature sensitive for protein synthesis, is specifically defective in vivo in its ability to charge tRNA with leucine. Cytoplasmic extracts exhibited temperature-sensitive leucyl-tRNA synthetase activity. It is, therefore, highly likely that the mutant has a structural alteration in leucyl-tRNA synthetase. The lowleakiness and low reversion rate of this mutant, combined with the specificity of the defect in its protein-synthesizing machinery, make i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…CHO cell line Asn-5 has a mutation in the asnS gene, which renders asparaginyl-tRNA synthetase thermolabile and the cells nonviable at 39°C (2). UCW 56 is derived from the CHO cell line tsH-1 and has a mutation in the leuS gene which results in leucyl-tRNA synthetase being thermolabile (27,32). This cell line is also nonviable at 39°C.…”
Section: Methodsmentioning
confidence: 99%
“…CHO cell line Asn-5 has a mutation in the asnS gene, which renders asparaginyl-tRNA synthetase thermolabile and the cells nonviable at 39°C (2). UCW 56 is derived from the CHO cell line tsH-1 and has a mutation in the leuS gene which results in leucyl-tRNA synthetase being thermolabile (27,32). This cell line is also nonviable at 39°C.…”
Section: Methodsmentioning
confidence: 99%
“…The wild-type Chinese hamster ovary cell line (CHO) and the temperature-sensitive mutant (tsH1) were maintained in suspension culture in a-minimal essential medium [16] supplemented with 1004 fetal calf serum as described by Thompson et al [15]. The growth temperature for both cell lines was usually 34 "C, although CHO cells were occasionally grown at 37 "C. Both CHO and tsHl cells were generous gifts of Dr C. P. Stanners (The Ontario Cancer Institute, University of Toronto, Toronto, Ont.…”
Section: Growth and Maintenance Of Cellsmentioning
confidence: 99%
“…Here we report a study with a mutant of the Chinese hamster ovary cell line (designated tsH1) shown previously by Thompson et ul. [15] to contain a temperature-sensitive leucyl-tRNA synthetase. At a non-permissive temperature, cytosolic protein synthesis was specifically inhibited and mitochondrial translation products could be selectively labelled.…”
mentioning
confidence: 99%
“…Thus far mutants have been isolated with alterations affecting the ribosome (6)(7)(8)(9), an elongation factor (10,11), and numerous aminoacyl-tRNA synthetases (12)(13)(14)(15)(16). The majority of the aminoacyl-tRNA synthetase mutants have been isolated from the Chinese hamster ovary (CHO) cell line.…”
Section: Introductionmentioning
confidence: 99%